An easy approach to obtain large piezoelectric constant in high-quality transparent ceramics by normal sintering process in modified potassium sodium niobate ceramics. Issue 8 (July 2020) - Rahman, Attaur; Park, Seonhwa; Min, Yuho; Hwang, Geon-Tae; Choi, Jong-Jin; Hahn, Byung-Dong; Cho, Kyung-Hoon; Nahm, Sahn; Ahn, Cheol-Woo
Abstract: It is well-known that the chemical modification of (K, Na)NbO3 (KNN)-based ceramics (KNNs) by the addition of Bi2 O3, or other aliovalent ions could decrease grain size and increases the crystal isotropic nature, namely, the pseudo-cubic phase since the sintered specimens could be transparent. However, due to the small grain size and pseudo-cubic phase, the transparent specimens have low piezoelectric properties. For obtaining better transparent and piezoelectric properties simultaneously, the starting KNNs composition must be selected with small grain size and high piezoelectric properties for Bi2 O3 modification. In this study, a high transmittance 52 % was measured at the wavelength of 800 nm, simultaneously with large piezoelectric constant (d33 = 125 pC/N) by normal sintering method in KNLTN + 1.5 mol.% Bi2 O3 composition. The origin of high transmittance simultaneously with large piezoelectric constant might be due to the small reduction in grain size, owing to the small grain size of starting KNLTN composition.